A Potential of Azolla sp. inclusion in Catfish (Clarias sp.) Feed Formulation Againts Energy Retention and Feed Conversion Ratio. - Puji Hariyanti; Prayogo .; Mirni Lamid (Airlangga University, 2017)
Catfish is one of the fish that has a high economical value. Catfish is accepted by society easily because of its advantages. These advantages include fast growing, good adaptive behavior, good taste, high nutrient, and cheap price. One of the factors that determine the success of aquaculture is the availability of adequate food, both quantity and quality. There are several alternative feed ingredients that can be used in the preparation of feed. One of these feed ingredients is azolla flour made from Azolla sp. plant. Azolla sp. plant contains large amount of protein up to 28,12% of its dried weight. Selection of the base material feed using Azolla sp. based on the research results Handajani (2000) which declare that the protein content Azolla sp. which is quite high, namely 28.12% dry weight. The addition of Azolla sp. in catfish feed formulation is expected to improve retention of energy and lower feed conversion ratio. The purpose of this study was to determine the addition of Azolla sp. in feed formulations affect the retention of energy and feed conversion ratio catfish. This research was conducted in July-August in the Faculty of Fisheries and Marine University Airlangga. Research method used in the study was an experimental method with complete random planning. It included five treatments and four repetitions. Treatments that were used included azolla flour inclusion 0%, 5%, 10%, 15% and 20% at the formulated feed. Data analysis that was used included statistic and descriptive. The result of the research shows that energy retention among treatments does not have significant difference. On the other hand, the feed conversion ratio also does not have significant difference. It can be concluded that Azolla sp. inclusion in the catfish feed formulation affects nothing to energy retention and feed conversion ratio. Keyword : Azolla sp., Clarias sp., Energy Retentiom, Feed Convertion Ratio